The Effectiveness of Woolwich Massage and Relaxation Music on Increasing Breast Milk Production: A Literature Review - Dewi Puspa Seruni; Muliatul Jannah (Sean Institute, 2026)
Background: Breast milk is a fluid produced by mothers as the best nutritional source for infants. A common problem faced by postpartum mothers is low milk production, and it is not uncommon for mothers to complain that they are unable to produce milk. One method to increase breast milk production is through Woolwich massage and music therapy. Woolwich massage and music therapy are effective non-pharmacological interventions for increasing breast milk production in postpartum mothers. Objective: to examine the effectiveness of Woolwich massage and relaxation music in increasing breast milk production in accordance with previous studies by reviewing several studies. Methods: this review used several sources, including a systematic search of computerized databases (Google Scholar) conducted over the last 5 years (2020-2025). Sixteen journals were obtained during the search, but after reviewing them according to the criteria and title suitability, only eight articles were used, consisting of seven national journals and one international journal. The keywords used in the search included “effectiveness of Woolwich massage”, “effectiveness of relaxation music”, and “increased breast milk production.”. Results: All studies show that Woolwich massage and music therapy are effective non-pharmacological interventions in increasing milk production in postpartum mothers. Conclusion: Woolwich massage and relaxation music have been proven effective in increasing milk production in postpartum mothers. Woolwich massage consistently shows a significant increase in milk volume and flow through the stimulation of prolactin and oxytocin, which strengthen the milk ejection reflex. Relaxation music helps reduce stress and increase comfort in mothers, thereby supporting an increase in the hormone oxytocin, which plays a role in the lactation process.